Peran Pemerintah Daerah dalam Menghadapi ACFTA - Purwanto, Erwan Agus (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2011)
This article discusses the implementation of Asean-China Fre Trade Area (ACFTA) and its consequences for the Indonesia economy. This article argues that its approval a decade ago, the Indonesian government showed sign of being unprepared to implement ACFTA. Data used in this article show that with the coming into force of ACFTA early 2011, a number of economic sectors have experienced negative growth, leading to the lay off of many workers in many sectors of the economy. To deal with this problem, the authors argue that local government and others stakeholders should be involve in effort to support Small-Scale and Medium Enterprise (SMEs) in strengthening their competitiveness. Doing so, requires local government to rescind various policies on SMEs considered inimical to their operation and adopt more business friendly e policies to support them.